UPAYA PENINGKATAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI DAN GIZI BAGI WANITA MENOPAUSE DI RT 05 RW 06 KELURAHAN LENGKONGSARI KECAMATAN TAWANG KOTA TASIKMALAYA - Sariestya Rismawati; Hermalia Putri, Dinda (Indra Institute Research & Publication, 2022)
Menopause is one of the stages in a woman's life characterized by a cessation of menstrual cycles. Menopausal symptoms will usually appear at the beginning of the menopause period. Some 22-63% of Asian women claim that they have complaints during menopausal period, including hot flush, camp system complaints, somatic symptoms, excessive night perspiration, and loss of libido. Besides reproductive health problems, increasing age is also one of the factors that trigger the problem of malnutrition. Frequent nutritional problems are loss of appetite, weight loss, change in taste senses, chewing disorders, swallowing disorders, constipation and difficulty in food access on the side often result in poor nutrition, overweight and obesity. The purpose of this activity is in an effort to increase in knowledge of reproductive and nutritional health during menopause. A method of executing public devotion used in the form of counseling. Following the implementation of this community's devoted activity increases in knowledge of reproductive health and nutrition during menopause. The suggestion to go forward to empowering women by increasing the knowledge of multiple resources to prepare for the menopause transition.